Factors affecting the maternal-foetal relationship - Čėsnaitė, Gerda; Domža, Gintautas; Ramašauskaitė, Diana; Volochovič, Jelena; Bužinskienė, Diana (Acta medica Lituanica, 2019)
Background. Mother’s attachment to her unborn child has a strong impact on a pregnant woman’s attitude towards her health, postnatal attachment, and the child’s physical and emotional growth. The purpose of our study was to identify the factors that impact the maternal-foetal relationship. Materials and methods. The study was conducted at the Centre of Obstetrics and Gynaecology of the tertiary-level Vilnius University Hospital Santaros Klinikos in Vilnius, Lithuania. An original questionnaire of nine parts was developed that the questionnaire included information on demographical data, gynaecological and obstetrical history, a relationship assessment scale, the index of happiness, an antenatal depression risk questionnaire, and the Maternal-Antenatal Attachment Scale. Results. The study included 388 pregnant women. It was found that the level of education, obstetrical issues during pregnancy, and the risk of postnatal depression negatively impacted the maternal-foetal relationship (p < 0.05). Mothers who were elder in family birth order, also those whose pregnancy was of a longer duration, who had a better-quality romantic relationship with partner, and whose socioeconomic fulfilment was higher were all found to have a better quality of maternal-foetal bonding (p < 0.05). Conclusions. The early recognition of low attachment and right application of various means of psychologic intervention might improve the quality of pregnancy, maternity, and childhood.